2021
DOI: 10.1177/10497323211065023
|View full text |Cite
|
Sign up to set email alerts
|

How Perceptions of Responsibility and Affective Consequences Influence Parents’ Digital Media Engagement in Relation to Human Papillomavirus Vaccination

Abstract: Individuals are expected to be responsible for their own health and that of their families—and act accordingly. Yet, being in a position of responsibility might be undesirable for individuals either unable or reluctant to comply with the expectations this responsibility entails. In this article, I explore how parents experience the process of engaging responsibly with digital media in relation to the question of human papillomavirus vaccination. The study is based on interviews with eighteen Danish parents, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…These cultural attitudes, also reflected in our study, can potentially culminate in a context predicted by Rogers and Pilgrim (1995) in which mass vaccination, rather than vaccination opposition, appears to be the historical anomaly (Hobson-West, 2007). Markedly, research by Nordtug (2022) identified that in a Western country like Denmark (or the United States in our study), individuals are expected to be responsible for their own health, whether they want to be or not. Some parents have reported feeling unprepared and overly burdened with this "responsibilization" to attempt to understand vaccine information on their own, preferring instead to place their trust in other actors, such as healthcare professionals, who are more knowledgeable, and effectively delegate the task of sifting through scientific vaccine information to make the right choice for their child.…”
Section: Theoretical Implicationssupporting
confidence: 61%
“…These cultural attitudes, also reflected in our study, can potentially culminate in a context predicted by Rogers and Pilgrim (1995) in which mass vaccination, rather than vaccination opposition, appears to be the historical anomaly (Hobson-West, 2007). Markedly, research by Nordtug (2022) identified that in a Western country like Denmark (or the United States in our study), individuals are expected to be responsible for their own health, whether they want to be or not. Some parents have reported feeling unprepared and overly burdened with this "responsibilization" to attempt to understand vaccine information on their own, preferring instead to place their trust in other actors, such as healthcare professionals, who are more knowledgeable, and effectively delegate the task of sifting through scientific vaccine information to make the right choice for their child.…”
Section: Theoretical Implicationssupporting
confidence: 61%
“…Interdisciplinary research poses certain ethical dilemmas, and questions as to when one is an expert on what is not set in stone. Reading information on a health authority's website does not make one an expert, but it might be argued that meeting some of the informants' unmet requests for information could help resolve some of their frustrations-especially for those for whom searching for such information themselves was a hurdle (Nordtug, 2022). In cases like this one, dilemmas thus also revolve around balancing obligations to help informants while not exceeding or trespassing outside one's own area of expertise.…”
Section: During Data Collection: Expert Trespassing Testimony During ...mentioning
confidence: 99%
“…The vaccine against HPV was introduced as a part of the Danish childhood vaccination program in 2009, and the introduction was initially successful (Sander et al, 2012; Suppli et al, 2018). However, a few years later, the vaccine came under considerable media scrutiny in Denmark, followed by a decline in vaccination uptake (Nordtug, 2022; Suppli et al, 2018). For the project, M.N.…”
Section: Cases Throughout the Research Processmentioning
confidence: 99%
“…Harper & Rail’s ( 2012 ) and Dolan’s ( 2014 ) respondents also resisted attributions of blame. Nordtug ( 2022 ) found that parents often felt overwhelmed by the onerous burden of their perceived responsibility for decision-making about their children receiving the human papilloma virus (HPV) vaccine, and thought health and media professionals should share in this burden.…”
Section: Responsibility: Our Perspective…and Our Subjects’mentioning
confidence: 99%